Peroxisome proliferator‐activated receptor‐γ signalling protects hair follicle stem cells from chemotherapy‐induced apoptosis and epithelial–mesenchymal transition. (1st January 2022) - Piccini, I.; Brunken, L.; Chéret, J.; Ghatak, S.; Ramot, Y.; Alam, M.; Purba, T.S.; Hardman, J.; Erdmann, H.; Jimenez, F.; Paus, R.; Bertolini, M.
Summary: Background Permanent chemotherapy‐induced alopecia (pCIA), for which preventive interventions remain limited, can manifest with scarring. While the underlying pathomechanisms of pCIA are unclear, depletion of epithelial hair follicle (HF) stem cells (eHFSCs) is likely to play a role. Objectives To explore the hypothesis that, besides apoptosis, eHFSCs undergo pathological epithelial–mesenchymal transition (EMT) in pCIA, thus explaining the scarring phenotype. Furthermore, we tested whether a peroxisome proliferator‐activated receptor (PPAR)‐γ modulator could prevent pCIA‐associated pathomechanisms. Methods Organ‐cultured human scalp HFs were treated with the cyclophosphamide metabolite 4‐hydroperoxycyclophosphamide (4‐HC). Additionally, HFs were pretreated with the agonistic PPAR‐γ modulator N ‐acetyl‐GED‐0507‐34‐Levo (NAGED), which has previously been shown to promote K15 expression and antagonize EMT in eHFSCs. Results In accordance with anticipated hair bulb cytotoxicity, dystrophy and catagen induction, 4‐HC promoted apoptosis along with increased p53 expression, DNA damage and pathological EMT in keratin 15 + (K15) eHFSCs, as evidenced by decreased E‐cadherin expression and the appearance of fibronectin + and vimentin + cells in the hair bulge. Pretreatment with NAGED protected against 4‐HC‐induced hair bulb cytotoxicity/dystrophy, and apoptosis, p53 upregulation and EMT in the bulge, thereby significantly preventing depletion of K15 + human eHFSCs ex vivo . Conclusions Since a key cyclophosphamide metabolite alone suffices to damage and deplete human scalp eHFSCs by promoting apoptosis, DNA damage and EMT ex vivo, strategies to prevent pCIA need to target these pathomechanisms. Given the ability of NAGED to prevent chemotherapy‐induced eHFSCs damage ex vivo, our study introduces the stimulation of PPAR‐γ signalling as a novel intervention strategy for the prevention of pCIA.